2016
DOI: 10.4103/0970-9290.191891
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of hydrogen peroxide bleaching agent on the shear bond strength of orthodontic brackets

Abstract: It was possible to conclude that 35% hydrogen peroxide bleaching agent does not affect the shear strength of orthodontic brackets bonded 24 h and 30 days after bleaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The present results demonstrated that three bleaching sessions increased the SBS of both types of brackets (monocrystalline and polycrystalline), corroborating the findings of other studies that verified higher SBS in previously bleached groups, when compared to without previous bleaching. 4 , 9 On the other hand, the study of Andrighetto et al 2 observed no differences in the SBS values in brackets bonded after bleaching or not bleached. Moreover, it was also possible to find reports contradicting the present findings, in which the SBS of brackets was higher in the groups without bleaching prior to bracket bonding.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The present results demonstrated that three bleaching sessions increased the SBS of both types of brackets (monocrystalline and polycrystalline), corroborating the findings of other studies that verified higher SBS in previously bleached groups, when compared to without previous bleaching. 4 , 9 On the other hand, the study of Andrighetto et al 2 observed no differences in the SBS values in brackets bonded after bleaching or not bleached. Moreover, it was also possible to find reports contradicting the present findings, in which the SBS of brackets was higher in the groups without bleaching prior to bracket bonding.…”
Section: Discussionmentioning
confidence: 92%
“…Dental bleaching is an easy and conservative therapy for whiting teeth. 1 , 2 Dental bleaching can be performed at-home or in-office, 3 - 5 and the most common used substances are carbamide and hydrogen peroxide in various concentrations. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that patients wait at least 7 or 14 days after bleaching before undergoing bracket bonding, to ensure the restoration of normal bond strength values (3,5). Although the negative influence of bleaching on bond strength has been confirmed (6)(7)(8), there is no consensus on the ideal interval between tooth whitening and bracket bonding to obtain effective adhesion of the brackets to enamel (5,(9)(10)(11)(12)(13). Therefore, the aim of this study was to evaluate the influence of the time interval between bleaching and bracket bonding on the shear bond strength (SBS) of orthodontic brackets bonded to enamel.…”
Section: Introductionmentioning
confidence: 99%
“…For a more accurate evaluation, the failure mode were analyzed by scanning electron microscopy (56). And the second null hypothesis that different storage media would not affect the failure mode on enamel and dentin of bleached tooth, was accepted.…”
Section: Discussionmentioning
confidence: 99%